2014
DOI: 10.1016/j.tig.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing regulation of telomerase: a new paradigm?

Abstract: Alternative splicing affects ~95% of eukaryotic genes, greatly expanding the coding capacity of complex genomes. Although our understanding of alternative splicing has increased rapidly, current knowledge of splicing regulation has largely been derived from studies of highly expressed mRNAs. Telomerase is a key example of a protein that is alternatively spliced, but it is expressed at very low levels, and although it is known that misregulation of telomerase splicing is a hallmark of nearly all cancers, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 77 publications
1
75
0
Order By: Relevance
“…However, while we observed increased transcription of exon 1 of h TERT , there must be additional mechanisms preventing the inclusion of exons critical to produce active telomerase. There is substantial evidence that alternative splicing of h TERT may also have a major role in suppressing the production of active telomerase in old cells [2224]. Furthermore, we performed 3D-FISH analysis in transformed SW26 and SW39 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while we observed increased transcription of exon 1 of h TERT , there must be additional mechanisms preventing the inclusion of exons critical to produce active telomerase. There is substantial evidence that alternative splicing of h TERT may also have a major role in suppressing the production of active telomerase in old cells [2224]. Furthermore, we performed 3D-FISH analysis in transformed SW26 and SW39 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cells with long telomeres at the end of chromosome 5p in young passaged cells form a chromatin loop in the region of the h TERT locus. Importantly, we demonstrated that the chromatin loop is disengaged in cells with short telomeres, leading to partial increased expression of h TERT mRNA during in vitro aging and in response to p21 knockdown; however, telomerase activity was not detected, and, alternatively, spliced variants were likely produced [17,2224,38]. Finally, we demonstrated that, in old cells with short telomeres, re-introduction of h TERT and elongation of telomeres results in a re-engagement of TPE-OLD.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic to the model is the long-held notion that telomeres undergo progressive erosion during the clonal expansion until telomerase is activated by mechanisms that might include telomerase reverse transcriptase gene (TERT) promoter mutations, transcriptional changes, epigenetic/chromatin modifications and splicing alterations [39]. Thus, telomerase activation during clonal expansion is permissive to the development of most cancers, as recently illustrated for the accumulating mutations in expanding nevi while they undergo successive stages of transformation into malignant melanoma [3].…”
Section: The Potential Resolution Of the Cancer-telomere Length Paradoxmentioning
confidence: 99%
“…The current accurate estimate for the quantity of catalytically active telomerase molecules is 50–100 per cell [42], produced from approximately 20 mRNA molecules per cell. The minority of the hTERT transcripts were spliced into the full-length isoform with telomerase activity [43]. A working explanation of these results was that the transcriptional machinery was not able to reduce the transcription to a level that produces only a few mRNA molecules within a single cell.…”
Section: Htert Pre-mrna Alternative Splicing Regulation In Cancer mentioning
confidence: 99%